Summer - Santrey, Louis; Sabin, Francene (Mahwah, N.J. : Troll Associates, 1983)
Text and photographs describe weather conditions, plant growth, and animal behavior that occur between spring and fall.
3.5
3-6
Keywords: Summer -- Juvenile literature; Seasons -- Juvenile literature; Summer; Seasons; Summer; Seasons; Summer; Seasons